A systematic review and secondary analysis of two studies identifying demographic and medical characteristics determining patient-centeredness in endometriosis care as experienced by patients. Issue 3 (22nd September 2020) - Schreurs, A M F; Dancet, E A F; Apers, S; van Hoefen Wijsard, M; Kuchenbecker, W K H; van de Ven, P M; Lambalk, C B; Nelen, W L D M; van der Houwen, L E E; Mijatovic, V
Abstract: STUDY QUESTION: What are the patient-specific determinants associated with patient-centered endometriosis care as measured by the ENDOCARE questionnaire (ECQ)? SUMMARY ANSWER: 'Overall grade for endometriosis care', 'educational level', 'membership of a patient organization' and 'having seen other specialists for endometriosis complaints' are correlated with overall patient-centeredness scores (PCS). WHAT IS KNOWN ALREADY: Patient-centeredness of endometriosis care can be evaluated using the validated ECQ. The ECQ leads to an overall PCS and separate PCS for 10 dimensions of endometriosis care. Previously, educational level and quality of life scores were found to be associated with ECQ results. STUDY DESIGN, SIZE, DURATION: First, a systematic literature review was performed (PROSPERO registration number: CRD42020169872). MEDLINE, Cochrane CENTRAL and EMBASE databases were searched from inception to May 2020 for studies in any language reporting on the results of the ECQ in patients with endometriosis. Two studies were identified. From the two studies, all original data were merged. In total, data from 546 patients were available for analysis. Second, univariate and multivariate regression analyses were performed to identify determinants for patient-centeredness of endometriosis care. PARTICIPANTS/MATERIALS, SETTING, METHODS: The two included studies evaluated patient-centeredness in four endometriosis care centers in Belgium and the Netherlands. All participants had surgically proven endometriosis. Possible patient-specific determinants were selected from the demographic and medical questions from the first part of the ECQ. These determinants were evaluated using linear regression analysis and all possible determinants with a P  > 0.2 in the univariate analysis were selected for stepwise multivariate analysis. Separate analyses were performed for overall PCS and each of the 10 dimensions. MAIN RESULTS AND THE ROLE OF CHANCE: The two included studies provided data from 546 patients. After adjustment for care center, multivariate analysis showed that a higher 'grade for endometriosis care' ( B  = 0.66), a 'lower educational level' ( B  = 0.50), 'being member of a patient organization' ( B  = 0.49) and 'having seen other specialists for endometriosis complaints' ( B  = 0.34) were independently associated with higher overall PCS ( R 2 = 0.41). 'Grade for endometriosis care' was a determinant for all dimensions of endometriosis care. 'Having seen other specialists for endometriosis complaints' was positively associated with the care dimensions 'respect for patients' values, preferences and expressed needs', 'continuity and transition' and 'technical skills'. Members of a patient organization showed higher scores on the care dimensions 'emotional support and alleviation of fear and anxiety', 'continuity and transition' and 'endometriosis clinic staff'. Furthermore, we found that having a higher level of education is associated with lower scores in the care dimensions 'physical comfort', 'emotional support and alleviation of fear and anxiety' and 'involvement of significant other'. LIMITATIONS, REASONS FOR CAUTION: These results delineate the patient-specific determinants of patient-centered care as measured using the Dutch ECQ. Whether results are generalizable to other countries should be investigated in an international study. This requires the ECQ to be validated in other languages first. WIDER IMPLICATIONS OF THE FINDINGS: The aforementioned determinants of patient-centered care are of value for studies benchmarking clinics for their patient-centeredness. In addition, they help clinicians to determine how to tailor their care to individual patients. At every visit, patients could be asked to grade the endometriosis care (on a scale of 0–10) to easily investigate patient-centeredness. When there is more time, women with endometriosis should be asked to complete the entire ECQ to investigate patient-centeredness in depth. STUDY FUNDING/COMPETING INTEREST(S): The department of reproductive medicine (involving C.B.L. and V.M.) of the Amsterdam UMC, Vrije Universiteit Amsterdam has received several research and educational grants from Guerbet, Merck and Ferring. The authors have no conflict of interest related to this manuscript.